Species diversity of Strigamia Gray, 1843 (Chilopoda: Linotaeniidae): a preliminary synthesis - Bonato, Lucio; Dányi, László; Socci, Antonio Augusto; Minelli, Alessandro (Zootaxa, 2012)
The centipede genus Strigamia Gray (Chilopoda: Geophilomorpha: Linotaeniidae) is revised with regards to morpholog-ical diagnosis, composition in known species, taxonomic nomenclature, major characters differentiating species, and geo-graphical distribution. Published information has been integrated and reinterpreted after direct examination of more thanhalf of the known species. The genus Strigamia is distinguished from similar genera (Agathothus Bollman, AraucaniaChamberlin, Damothus Chamberlin, Zantaenia Chamberlin) mainly by the conspicuous basal denticle of the forcipulartarsungulum, the paired ventral pore areas on the posterior part of trunk segments, and the remarkably swollen ultimatepair of legs in adult males. At least 32 distinct species are known and another 12 are recognized provisionally, whereas 21names are rejected as synonyms. Of all other nominal species that have been referred to Strigamia or its synonyms in thepast, 16 are shown not to actually belong to Strigamia and another 4 remain uncertain as to their generic assignment. Spe-cies of Strigamia differ mainly in the shape of the forcipular tarsungulum and denticle, average number of legs (overallrange from 31 to 83 pairs, possibly to 91), aspect of pleuropretergite and shape of metasternite of the ultimate leg-bearingsegment, and the arrangement of coxal pores. Strigamia as a whole inhabits the most part of the temperate Holarctic, butreaches southwards to the Indochinese region. The following new synonymies are introduced: Leptodampius Chamberlin,1938 = Korynia Chamberlin, 1941 = Strigamia Gray, 1843; Scolioplanes engadinus banaticus Verhoeff, 1935 = S. acum-inata (Leach, 1815); Scolioplanes mediterraneus Verhoeff, 1928 = S. crassipes (C.L. Koch, 1835). The following newcombinations are introduced: Strigamia auxa (Chamberlin, 1954), S. carmela (Chamberlin, 1941), S. texensis (Chamber-lin, 1941), S. tripora (Chamberlin, 1941), all from Korynia; S. exul (Meinert, 1886), S. sacolinensis (Meinert, 1870), S.sibirica (Seliwanoff, 1881), S. sulcata (Seliwanoff, 1881), all from Scolioplanes Bergsøe & Meinert; S. fusata (Attems,1903) from Diplochora Attems; S. lampra (Chamberlin, 1938) from Leptodampius; S. munda (Chamberlin, 1952) fromLinotaenia C.L. Koch; S. svenhedini (Verhoeff, 1933) from Paraplanes Verhoeff; S. urania (Crabill, 1954) from Tomotaenia Cook, 1895.